2017
DOI: 10.1074/mcp.m117.067355
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic Analysis Reveals the Importance of Kinase Regulation During Orbivirus Infection

Abstract: Bluetongue virus (BTV) causes infections in wild and domesticated ruminants with high morbidity and mortality and is responsible for significant economic losses in both developing and developed countries. BTV serves as a model for the study of other members of the Orbivirus genus. Previously, the importance of casein kinase 2 for BTV replication was demonstrated. To identify intracellular signaling pathways and novel host-cell kinases involved during BTV infection, the phosphoproteome of BTV infected cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
1
11
0
Order By: Relevance
“…Moreover, our data provide a molecular basis for this activity through the identification of BRAF as a new interactor of BTV-NS3, together with the fact that BRAF silencing impairs BTV-activated MAPK/ERK signaling. Intriguingly, two other studies have shown that BTV does not activate the MAPK/ERK pathway (38,39). However, these findings do not necessarily contradict our current data.…”
Section: Btv-ns3 Inhibits the Induction Of Ifn-␣/␤ Independently Of Msupporting
confidence: 60%
“…Moreover, our data provide a molecular basis for this activity through the identification of BRAF as a new interactor of BTV-NS3, together with the fact that BRAF silencing impairs BTV-activated MAPK/ERK signaling. Intriguingly, two other studies have shown that BTV does not activate the MAPK/ERK pathway (38,39). However, these findings do not necessarily contradict our current data.…”
Section: Btv-ns3 Inhibits the Induction Of Ifn-␣/␤ Independently Of Msupporting
confidence: 60%
“…We measured CK2 activity indirectly by using an antibody against the phospho-CK2 substrate (motif pS/pTDXE) to measure the amount of phosphorylated CK2 substrates. This method is widely used in literature to measure kinase activity, such as activity of the following kinases CK2 [ 16 , 49 , 50 , 51 , 52 ], AMPK [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ], AMT/ATR [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ], PKA [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], and PKC [ 77 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Both CK2 knockdown and CX-4945 treatment inhibited the proliferation of CCA cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SILAC [ 29 ] have overcome some of the phosphoproteomics quantification problems and improved the insights obtained. [ 23,30 ]…”
Section: Introductionmentioning
confidence: 99%